Stakeholder influence on global warming potential of reinforced concrete structure. (December 2021) - Belizario-Silva, Fernanda; Galimshina, Alina; Reis, Daniel Costa; Quattrone, Marco; Gomes, Beatriz; Marin, Marcelo Cuadrado; Moustapha, Maliki; John, Vanderley; Habert, Guillaume
Abstract: Reducing the embodied carbon of reinforced concrete structures is crucial to mitigate climate change. Several stakeholders in the construction value chain can contribute to this effort. Therefore, this work quantifies the influence of various decisions made by different stakeholders on the global warming potential (GWP) of a reinforced concrete structure. These decisions include the structural design, material embodied impact, transportation distances, and construction practices. Herein, each decision is modelled as an uncertainty source and its contribution to the total uncertainty of the structure's GWP is assessed. Two scenarios are considered: business-as-usual, which only considers conventional concrete mix design, and an innovation scenario, which also considers the option of high-filler low-water concrete. In the business-as-usual scenario, the structure's GWP varies from 162 t CO2e to 324 t CO2e, and the most influential decision is the structural design, which accounts for 59% of the total uncertainty, followed by decisions associated with materials production and supplier selection. Meanwhile, in the innovation scenario, the structure's GWP varies from 124 t CO2e to 324 t CO2e, wherein the choice between conventional and the innovative concrete mix design is the most influential decision, contributing 59% of the total uncertainty. Overall, the relative importance of stakeholders can be identified to prioritise improvement measures, including implementing innovative technologies. Graphical abstract: Image 1 Highlights: Influence of stakeholder decisions on GWP of a concrete structure is quantified. GWP varies 293 kg CO2e /m 2 when only conventional technologies are considered. Structural design decisions account for 59% of this variation. Innovative concrete formulation technology raises the variation to 360 kg CO2e /m 2 . Concrete formulation decisions account for 59% of the variation in the latter scenario.